Beban Kerja dan Kualitas Layanan Perawat pada Tindakan Pemasangan Infus di Rumah Sakit - Sitti Mukminan; Andi Mappanganro; Haeril Amir (Window of Nursing Journal, 2026)
Workload is an important factor that can be seen from the provision of health services in hospitals, one of which is intravenous administration, be it intravenous insertion or injection drug administration through an IV tube. The purpose of this study was to determine the relationship between workload and the quality of nurse services in the infusion installation action at Ibnu Sina YW-UMI Hospital Makassar. The design in this study used a cross-sectional design, a sampling technique using purposive sampling with a total of 51 respondents in the ER and Treatment Room. The data analysis used in this study is statistical analysis of Chi-Square Test. The results of the study from univariate data analysis and bivariate analysis showed that there was a workload relationship to the quality of nurse services in the infusion installation procedure with a p value of 0.042 < 0.05. The conclusion in this study is that there is a relationship between workload and the quality of nurse services in the infusion procedure. Therefore, it is expected that the heavy workload does not affect the quality of nurse services on the follow-up of infusion installation. Advice in this study is expected for nurses to maintain the quality of service, one of which is the infusion insertion.